DETECTING FUTURE TRENDS OF HIV PREVALENCE AMONG INDIVIDUALS AGED 15-49 YEARS IN GUINEA USING HOLT’S LINEAR METHOD (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Guinea from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will slightly decline over the out of sample period. Therefore, it is vital to address major drivers of HIV transmission among this age group, improve ART retention & ART adherence among people living with HIV and monitoring the emergence of drug resistant HIV strains.